Cytokine secretion by decidual lymphocytes in transient hypertension of pregnancy and pre-eclampsia. - Wilczyński, Jacek R (2002)
BACKGROUND: Transient hypertension (TH) and preeclampsia (PE) are believed to have different pathophysiology. However, 15-25% of pregnant women initially diagnosed as having TH develop PE. To clarify the immuno-pathogenetical connections between the two syndromes, we studied the pattern of T helper cell (Th)1/Th2 cytokine balance disturbances existing inside maternal decidua in normal pregnancy (NP) and pregnancies complicated with TH and PE. METHODS: Third-trimester decidual tissue was obtained by curettage of uterine cavity during elective caesarean sections in NP (n = 11), TH (n = 17) and PE (n = 21) patients. Cell suspensions were prepared by an electromechanical dispersal method and centrifugated using a standard gradient sedimentation technique. Isolated lymphocytes were placed in medium (RPMI 1640, 10% fetal calf serum, L-glutamine, penicillin, streptomycin) and cultured for 72 h with or without mitogen phytohaemaglutinine (PHA). The enzyme-linked immunosorbent assay method was used for estimation of interleukin (IL)-2, IL-4, IL-6, IL-10, IL-12 and interferon-gamma (IFN-gamma) in culture supernatant. STATISTICAL ANALYSIS: The Kruskal-Wallis and the Mann-Whitney U tests were used (p < 0.05). RESULTS: Both spontaneous and PHA-stimulated secretion of Th2-type cytokines IL-6 and IL-10 was decreased in PE patients compared with TH and NP patients. The concentration of Th1-type cytokine IFN-gamma was increased in patients suffering both from TH and PE. CONCLUSION: On the base of decidual cytokine secretion, both PE and TH are syndromes of local Th1/Th2 cytokine balance disturbances as compared with NP, and TH seems to be an intermediate step to PE.